2015
DOI: 10.1007/s11102-015-0675-0
|View full text |Cite
|
Sign up to set email alerts
|

Extended transsphenoidal approach for pituitary adenomas invading the cavernous sinus using multiple complementary techniques

Abstract: Extended transsphenoidal surgery incorporating multiple complementary techniques was highly effective for PAs invading the CS. Postoperative complications rates were relatively low, especially for patients undergoing initial surgery and those with Knosp Grade 3 tumors. Total resection of PAs invading the CS remains challenging, especially in patients undergoing reoperation or having firm tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
(63 reference statements)
1
19
0
Order By: Relevance
“…However, the reported rates of GTR of pituitary macroadenomas with CSI vary tremendously among different groups and range from 0% to 92.3%. 2,3,9,10,19,24 This variability may be partly due to the differing levels of experience among operating surgeons. 11 In our study, the GTR rate decreased with higher Knosp grade, regardless of whether the Knosp grades were derived from VIBE or CISS images.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reported rates of GTR of pituitary macroadenomas with CSI vary tremendously among different groups and range from 0% to 92.3%. 2,3,9,10,19,24 This variability may be partly due to the differing levels of experience among operating surgeons. 11 In our study, the GTR rate decreased with higher Knosp grade, regardless of whether the Knosp grades were derived from VIBE or CISS images.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most nonfunctioning PAs extending into the cavernous sinus are neither aggressive nor invasive, and cavernous sinus extension of PAs may be caused by weakness of the medial wall of the cavernous sinus (16). In our case series, total resection through extended transsphenoidal surgery was achieved for a substantial number of invasive Pas, with no recurrence after a long followup time (Figure 1) (17). Overall, a more accurate definition and objective diagnostic criteria are needed.…”
Section: Definition Of Refractory Pamentioning
confidence: 83%
“…In most reports, the extent of tumor removal in cases of pituitary adenoma invasion of the CS has been discussed in relation to the Knosp grade. 20,[28][29][30][31][32][33][34][35][36][37][38][39] However, a recent systematic review revealed that intraoperative CS invasion as judged during endoscopic surgery was different to the preoperative radiographic estimation of Knosp grade. 18 Hence, it may not be appropriate to discuss the removal rate of CS invasion in pituitary tumor cases with an estimated Knosp grade.…”
Section: Discussionmentioning
confidence: 99%